Gondang Hasapi in Holding Ritual Parmalim Si Pahasada (Study of the Shapes of Gondang and its Functions) - Esra P.T Siburian (BIRCU, 2019)
This paper aims to discuss the existence of a form of gondang at the ritual ceremony of Si Pahasada, and how its function at the ritual ceremony of Si Pahasada in Huta High of North Sumatra is the subject matter to be discussed. The method used in this study is by using descriptive qualitative method. Collecting data is done through observation, interview, documentation, and bibliography. In this study it is found that there are 12 dishes reportoar gondang kesumpaan presented during this ritual. In this study also found eight functions of gondang in the ritual of Parmalim Si Pahasada, namely: 1) Aesthetic function, 2) communication functions, 3) symbolic functions, 4) physical response function, 5) enforcing social norms, 5) validation of social institutions. 6) religious ritual function, 7) cultural continuity and stability, 8) contribution to community integration.